Intelligent path guidance robot for blind person assistance - Toha, Siti Fauziah; Md Yusof, Hazlina; Razali, Mohd Fakhruddin; Abdul Halim, Abdul Hadi (Center for Natural Science & Engineering Research (CNSER) ; IEEE, 2015)
Visually impaired person faced difficulty in limited movement, even in their house. A study on this field based on engineering concept is vital to help the visually impaired people. It is very important that this research come out with an intelligent path guidance robot to assist the visually impaired people in their movement. This paper presents the design and implementation of an intelligent path guidance robot to assist the visually impaired people in their movement (iPath). The robot has the capability to follow a path that is provided on the floor and also detect any obstacle that is blocking the path. Apart from that, the robot can sense the motion of the user. The robot can also detect when the user wants the robot to increase or decrease its speed. Another great advantage of the robot is that the cane that is attached on the robot can be easily detached from the robot body. In addition, the hardware design for the robot is small and lightweight. Thus, visually impaired people can comfortably receive the help from the robot in assisting their movement.